2018
DOI: 10.5892/ruvrd.v16i1.3880
|View full text |Cite
|
Sign up to set email alerts
|

A Saúde Bucal Na Percepção Dos Usuários De Um Restaurante Popular Localizado Em Uma Cidade Médio Porte Da Paraíba

Abstract: A prevenção em odontologia tem tido ênfase ultimamente. Os cuidados com a saúde bucal têm ido além da visão estética. O presente estudo visa avaliar a autopercepção da saúde bucal dos usuários do Restaurante Popular da Cidade de Patos/PB. Trata-se de um estudo transversal, foi aplicado um questionário com questões abordando variáveis socioeconômicas e sobre saúde bucal. Em seguida os dados foram analisados através do software Statistical Package for the Social Sciences (SPSS) versão 22.0. Foram avaliados 252 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Oliveira et al [44] Evaluate the self-perception of the oral health of the customers of the popular restaurant located in Patos-PB.…”
Section: Gomes Et Al [12]mentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al [44] Evaluate the self-perception of the oral health of the customers of the popular restaurant located in Patos-PB.…”
Section: Gomes Et Al [12]mentioning
confidence: 99%
“…The 19 studies, whose objective was to outline the profile of users, used analyzes of socioeconomic, sanitary, anthropometric and food indicators, as well as their level of food security [12,24,25,27,29,[31][32][33][34][35]37,39,41,42,44,45,[48][49][50]. Most studies identified the following users' profile: men, married, with or without children, with an educational level up to high school, and income mainly between half of the minimum wage and the minimum wage, with variations up to two times the minimum wage [12,24,25,27,31,32,34,35,41,44,45]. Still, five studies identified the prevalence of overweight and obesity in users, with percentages ranging between 42.9% and 53.2% [25,27,32,35,45].…”
Section: Popular Restaurants Users' Profilementioning
confidence: 99%